1990
DOI: 10.1037/0096-1523.16.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of judging time to arrival: Effects of modality, trajectory, and gender.

Abstract: Observers' accuracy in using time-to-arrival (Ta) information was examined in 4 experiments. The issues included use of visual vs. acoustic Ta information, use of acoustic Ta information by blind Ss, use of Ta information controlling for velocity, and effects of angle of approach and arrival time on judgment accuracy. Visual information was used more efficiently than audiovisual and auditory information. Blind Ss used acoustical approach information as accurately as sighted Ss used visual information. Radial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

49
345
6
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(402 citation statements)
references
References 36 publications
49
345
6
2
Order By: Relevance
“…Second, combining auditory and visual inputs did not result in higher accuracy (deviation of estimates from the veridical value) or greater precision (variability of the estimates) than in the unimodal conditions. This result is consistent with Schiff and Oldak (1990;but see Zhou et al, 2007). However, the regression analyses showed that both auditory and visual information was used (Prime & Harris, 2010), although visual information was weighted more heavily than auditory information.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Second, combining auditory and visual inputs did not result in higher accuracy (deviation of estimates from the veridical value) or greater precision (variability of the estimates) than in the unimodal conditions. This result is consistent with Schiff and Oldak (1990;but see Zhou et al, 2007). However, the regression analyses showed that both auditory and visual information was used (Prime & Harris, 2010), although visual information was weighted more heavily than auditory information.…”
supporting
confidence: 82%
“…Specifically, we performed analyses to determine the extents to which visual τ, θ final , ⋅ θ final , Δθ, and D final v were used in such judgments. It is known that individuals can use auditory information alone to make TTC estimates and that blind individuals can use acoustical TTC information with accuracy comparable to sighted individuals' abilities to use visual TTC information (Schiff & Oldak, 1990). In the auditory domain, accurate TTC information is reliably provided about objects travelling on a straight path at a constant velocity by a τ-like ratio of the objects' instantaneous acoustic intensity to its instantaneous rate of change in intensity (Jenison, 1997;Shaw, McGowan, & Turvey, 1991).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Underestimation of time-to-contact, however, would lead to the qualitative features of the angle of approach effect observed in Experiments 2a and 2b. Indeed, a number of studies in which the viewing period was terminated before the object actually arrived at the point of observation, demonstrate underestimation of the time remaining until arrival (e.g., Cavallo & Laurent, 1988;McLeod & Ross, 1983;Schiff & Detwiler, 1979;Schiff & Oldak, 1990). This hypothesis, that the angle of approach effect was due to an underestimation of time remaining, was addressed in Experiment 3.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that demonstrated progressive underestimation of time-to-contact with increasing estimation interval magnitudes typically involved such an estimation (e.g., Cavallo & Laurent, 1988;McLeod & Ross, 1983;Schiff & Detwiler, 1979;Schiff & Oldak, 1990). At various times before the approaching object would have reached the observer, the presentation was terminated and the subject was required to indicate the time until arrival.…”
Section: Discussionmentioning
confidence: 99%